Hubungan Status Sosial Ekonomi dengan Tingkat Konsumsi Fast Food pada Remaja - Musparlin Halid; Toto Sudargo (Universitas Islam Negeri Mataram, 2016)
Modernization has brought negative impact to the public, including in adolescents directly or indirectly, that has directed the diversion a healthy diet. Adolescent are required to more selective in choosing food products consumed. Fast food is food containing high in calories, fat and low fibers. To know the relationship of socioeconomic status with fast food consumption levels among adolescents in Mataram city. The study was observational studies with cross sectional design. The samples as many as 373 students. Dependent variable was the consumption of fast food, and the independent variable was socioeconomic status. The instruments used were questionnaire and FFQ. Data analysis by means of descriptive, and Chi Square test (χ²). Based on the duration per week, there was a relationship between socio-economic status with the western fast food consumption levels (p = 0.00) and local fast food (p = 0.00). Moreover, adolescents with prosperous socioeconomic status have a higher consumption of fast food was very high with a duration of 1 time/week and 2 times/week. While based on the frequency, there was a significant relationship between socioeconomic status with western fast food consumption levels with p = 0.00 and local fast food with p = 0.00 influence of friends was significant with western fast food consumption levels in adolescents (p = 0.002). The habit of eating at home (lunch with p = 0.007) and the effect of mass media was significant with the local fast food consumption levels (p = 0.04). Adolescents with a prosperous socioeconomic status have greater opportunities to consume fast food than in adolescents with socioeconomic status were less prosperous.